Meningkatkan Kinerja Pemasaran Hotel dengan Memanfaatkan Nilai Pelayanan Ergo-ikonik - Andriyansah Andriyansah; Fatia Fatimah; Zainur Hidayah; Anshar Daud (Universitas Muhammadiyah Sidoarjo, 2020)
The present study aims to support the hypotheses proposed in the research model to prove the fact that the suggested variables can contribute towards performance improvement. The study offers a novel variable namely ergo-iconic service value. The object of this study includes 118 three-star hotels located in the business districts of the Special Capital Region of Jakarta and West Java. The study used questionnaires that were distributed to hotel managers to acquire research data. The ergo-iconic service value as a mediating variable is proven to improve the marketing performance of the hotels. Other variables, namely, the ability to implement management system certification and the ability to adapt to technology also increase the mediating role of ergo-iconic service value. The hypotheses are empirically proven as all three variables successfully improved the hotels' marketing performance. The current research also shows that the role of humans is still significant, and human presence is required to improve performance despite the fact that we are currently at the Industry 4.0 era; in this case, not all activities should be taken over by robots.